KUALITAS SUPLEMEN BAHAN AJAR CETAK PROGRAM STUDI S1 PENDIDIKAN GURU PENDIDIKAN ANAK USIA DINI (BERDASARKAN PERSEPSI MAHASISWA DI UPBJJ-UT JAKARTA, SERANG, DAN BANDUNG) - Tatminingsih, Sri; Amini, Mukti; Setiawan, Denny (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2011)
This research was aimed to access the quality of non printed learning materials especially video as a supplement for learning modules offered by undergraduate study program of early childhood education (PGPAUD). Data were collected by using questionnaire with 86 closed-ended questions and one open-ended question. Students in their third, forth, and fifth semester from Jakarta, Serang, and Bandung were taken as samples. Among 90 questionnaires distributed, about 69 (76.67%) were returned. Descriptive analysis was employed in this research. It was concluded that the technical quality of the Video Program including sounds, colors, packaging, duration, captions, utilization, and documentation, were good. The quality of instruction in that video was good as well. In addition, the Video Program has high quality content. The respondents also agreed that the Video Program was useful for them as kindergarten teachers. However it was stated that the Video Program was only a little helps in doing their course examination. Meanwhile, the average students score for this subject is B and C.